Design thinking in Education: Empowering students in ELT class - Rimajon Sotlikova (UM Purwokerto Press, 2023)
This article explores the integration of Design Thinking into English Language Teaching (ELT) classrooms as a means to empower students. Design Thinking, a dynamic problem-solving framework, offers a student-centred approach to education that places learners at the forefront. This article further investigates the ideation phase, where creativity in language use is encouraged through technology integration and interactive activities. These practices align with 21st-century skill development, promoting creativity, critical thinking, and effective communication. Prototyping, another crucial Design Thinking stage, finds application in project-based learning activities that tangibly reinforce language skills while offering real-world context. The author explores the theories of testing phase that empowers students to apply language competence beyond the classroom, emphasizes the practical value of language acquisition. By examining the confluence of Design Thinking principles with ELT, this article discusses the potential to prepare students as not only proficient communicators but also as adaptable thinkers ready to navigate our interconnected world. Design Thinking, therefore, emerges as a powerful tool for transforming ELT classrooms into hubs of innovation and student empowerment.